A Study on the Rate of Events and Water Loss in Water Distribution Network of Azna, Lorstan, Iran during 2008-2014 and Its Associated Factors - Mohammad Adeli; bahram Kamarehie; Reza Jalilzadeh yengejeh; Zainab Rostami (Mazandaran University of Medical Sciences, 2016)
Introduction and purpose: One of the problems of water distribution systems is loss of large volumes of water due to the occurrence of various events, which incurs a huge financial loss. Regarding this, the aim of the present study was to investigate the rate of events and water loss in the water distribution system and its related factors in Azna, Lorestan province, Iran, during 2008-2014. Methods: This cross-sectional study was conducted using census method, surveys, and field data collection. The amount of water production and consumption, the volumes of water loss, the number of accidents, type of pipe, pressure zone, as well as the age and length of the pipes recorded during 2008- 2014 were studied and analyzed. Results: According to the results, the highest (34.48%) and lowest (20.57%) amount of water losses happened in 2008 and 2014, respectively. High pressures in water systems had significant relationship with the number of events as well as the amount of water loss and water consumption. In addition, higher length and age of the pipes had a direct correlation with increased number of events and water loss. Furthermore, the maximum number of events were found to occur in the pipe embranchment and galvanized pipes. Conclusion: This study showed that of events was directly related to the length and age of the pipes, the water pressure, and number of branches. Also water loss quantity can be reduced by applying suitable management techniques in different sections. Furthermore, the water loss can be significantly controlled by taking such measures as reducing the pressure in the high-pressure zones, timely replacement of old and inappropriate pipes, appropriate fixing of the pipes, replacement of the galvanized pipe, and standard implementation of pipes and fittings.